2008
DOI: 10.1021/ol802021w
|View full text |Cite
|
Sign up to set email alerts
|

Sintokamides A to E, Chlorinated Peptides from the Sponge Dysidea sp. that Inhibit Transactivation of the N-Terminus of the Androgen Receptor in Prostate Cancer Cells

Abstract: The new chlorinated peptides sintokamides A to E (1-5) have been isolated from specimens of the marine sponge Dysidea sp. collected in Indonesia. Their structures were elucidated by a combination of spectroscopic and single-crystal X-ray diffraction analyses. Sintokamide A (1) is an inhibitor of N-terminus transactivation of the androgen receptor in prostate cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
161
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(170 citation statements)
references
References 23 publications
2
161
0
1
Order By: Relevance
“…EPI-001 also inhibited constitutively active AR devoid of an LBD [35], which implies that it may have use in combating the splice variants of the AR that may mediate abiraterone resistance. EPI-001 does not reduce levels of AR protein nor does it prevent nuclear translocation of the AR in response to androgen [35]. Other androgen-directed agents that are in development include AR antagonists (ODM-201, Clinicaltrials.gov NCT01317641) and AR production inhibitors (ZD 3514, Clinicaltrials.gov NCT01162395).…”
Section: Future Directionsmentioning
confidence: 97%
See 2 more Smart Citations
“…EPI-001 also inhibited constitutively active AR devoid of an LBD [35], which implies that it may have use in combating the splice variants of the AR that may mediate abiraterone resistance. EPI-001 does not reduce levels of AR protein nor does it prevent nuclear translocation of the AR in response to androgen [35]. Other androgen-directed agents that are in development include AR antagonists (ODM-201, Clinicaltrials.gov NCT01317641) and AR production inhibitors (ZD 3514, Clinicaltrials.gov NCT01162395).…”
Section: Future Directionsmentioning
confidence: 97%
“…Deletion experiments have shown that the N-terminal domain is essential for transcriptional activity of the AR in response to ligand as well as in the absence of ligand [34]. EPI-001 inhibits AR activity induced by a variety of non-canonical activators such as forskolin, IL-6, and by factors secreted by osteoblasts (bone-derived factors [35]). EPI-001 also inhibited constitutively active AR devoid of an LBD [35], which implies that it may have use in combating the splice variants of the AR that may mediate abiraterone resistance.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Senyawa celebesides A dan C tersebut mempunyai aktivitas sebagai anti tumor dan anti ?HIV. Senyawa Sintokamide A yang merupakan inhibitor transaktivasi N?terminal dari reseptor androgen pada kanker prostate telah diisolasi oleh Sadar et al (2008) dari spons Dysidea sp. asal Indonesia.…”
Section: Pendahuluanunclassified
“…Also, there are two new classes of small molecules isolated from sponge (Dysidea sp.) extract that exhibit anti-AR activity (Andersen et al, 2010;Quayle et al, 2007;Sadar, 2011;Sadar et al, 2008). One type of these sponge compounds are small chlorinated peptide called sintokamides, and the other is EPI-001 (i.e., bisphenol A diglycidic ether.HCl.H 2 O).…”
Section: Overexpressed Ar and Ar Variants In Crpc As Therapeutic Targetsmentioning
confidence: 99%